2020
DOI: 10.1002/acn3.51034
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regression and mitochondrial function in children with autism

Abstract: Background: Developmental regression (DR) occurs in about one-third of children with Autism Spectrum Disorder (ASD) yet it is poorly understood. Current evidence suggests that mitochondrial function in not normal in many children with ASD. However, the relationship between mitochondrial function and DR has not been well-studied in ASD. Methods: This cross-sectional study of 32 children, 2 to 8 years old with ASD, with (n = 11) and without (n = 12) DR, and non-ASD controls (n = 9) compared mitochondrial respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 50 publications
(65 reference statements)
6
40
1
Order By: Relevance
“…We have suggested that this may represent a model of mitochondrial associated NDR as mitochondrial function is lost with a mild increase in ROS in the AD-A LCL model and NDR is known to be associated with triggers that increase physiological stressor which can increase ROS. In fact, a recent study examining mitochondrial function in PBMCs in children with ASD in a manner similar to the current study found that those with a history of NDR demonstrated elevated respiratory rates, similar to our LCL model, as compared to those without a history of NDR [25].…”
Section: Parallels With Laboratory Models Of Mitochondrial Dysfunctiosupporting
confidence: 84%
See 1 more Smart Citation
“…We have suggested that this may represent a model of mitochondrial associated NDR as mitochondrial function is lost with a mild increase in ROS in the AD-A LCL model and NDR is known to be associated with triggers that increase physiological stressor which can increase ROS. In fact, a recent study examining mitochondrial function in PBMCs in children with ASD in a manner similar to the current study found that those with a history of NDR demonstrated elevated respiratory rates, similar to our LCL model, as compared to those without a history of NDR [25].…”
Section: Parallels With Laboratory Models Of Mitochondrial Dysfunctiosupporting
confidence: 84%
“…In general, separate variables were used for (1) environmental exposure, (2) mitochondrial energy production, (3) mitochondrial oxidative stress control, (4) redox metabolism (both iGSH and iGSSG), (5) cognitive neurodevelopment, (6) behavior and (7) age of NDR in the models for those with NDR. These models did introduce measures of redox metabolism since it is so important in regards to mitochondrial function in ASD [64], especially with respect to NDR [25,26,30,31], and is a prominent physiological abnormality found in ASD [53,65,66]. Since ASD behavior depended on neurodevelopment in the regression models above as well in our previous studies [40,41], a relationship between neurodevelopment and behavior was considered in the models and was found to be significant in every model.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is linked to ASD. A systematic meta-analysis study showed that the prevalence of mitochondrial diseases in ASD was 4–5%, which is markedly higher than the general population (around 0.01%) [ 126 , 127 ]. Lactate was the first biomarker that was found to be elevated in ASD children’s serum [ 126 , 127 ].…”
Section: Mitochondria Dysfunction In Asdmentioning
confidence: 99%
“…A systematic meta-analysis study showed that the prevalence of mitochondrial diseases in ASD was 4–5%, which is markedly higher than the general population (around 0.01%) [ 126 , 127 ]. Lactate was the first biomarker that was found to be elevated in ASD children’s serum [ 126 , 127 ]. Other mitochondrial biomarkers that were shown to be elevated in children with ASD are AST, pyruvate, and creatine kinase [ 126 , 128 ].…”
Section: Mitochondria Dysfunction In Asdmentioning
confidence: 99%
“…Interestingly, abnormal mitochondrial metabolism has been linked to ASD. 70 73 Clinical 74 and basic research studies 75 suggest that folate is important in mitochondrial function. In a recent study, our group measured the function of several mitochondrial enzymes in children with ASD who were receiving various supplements that could influence mitochondrial function.…”
Section: Folate Improves Mitochondrial Function In Children With Asdmentioning
confidence: 99%